1995
DOI: 10.1088/0953-4075/28/7/013
|View full text |Cite
|
Sign up to set email alerts
|

L-shell X-ray production by 2-12 MeV carbon ions in fifteen selected elements from copper to lead

Abstract: L-shell X-ray production cross sections for 29Cu, 31Ga, 32Ge, 35Br, 39Y, 42Mo, 47Ag, 50Sn, 57La, 60Nd, 64Gd, 67Ho, 70Yb, 79Au and 82Pb were measured for carbon ions in the 2-12 MeV energy range. The copper to yttrium data were previously measured using a Si(Li) detector with a beryllium window, while the molybdenum to lead X-rays were counted with a windowless Si(Li) detector, whose efficiency was determined by various normalization techniques. The measured X-ray cross sections are compared to predicted X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…[26], replacement of the projectile atomic number Z 1 with its charge state q, the probability P of ionizing an outer shell electron is calculated according to Eq. (A3) of Ref.…”
Section: Extraction Of X-ray Production and L-subshell Ionizationmentioning
confidence: 99%
“…[26], replacement of the projectile atomic number Z 1 with its charge state q, the probability P of ionizing an outer shell electron is calculated according to Eq. (A3) of Ref.…”
Section: Extraction Of X-ray Production and L-subshell Ionizationmentioning
confidence: 99%
“…A comparison of the M x-ray cross section measurements of Pb and Bi of earlier workers with the corresponding theoretical values indicates that there is a good agreement between the experimental results and the PWBA theory for protons and 4 He + ions (Busch et al 1973, Gowda andPowers 1985). Some of the other workers (Mehta et al 1982, de Castro Faria et al 1983, Price et al 1988, Pajek et al 1990a have, however, observed that the first Born theory always tends to over-predict the cross sections at all energies for protons and the other incident ions such as 3 He + , 4 He + and Be + , while the ECPSSR theory has been found to give the best overall description, although it tends to under-predict the data at very low energies (< 1 MeV). For C-, O-and F-ion impact the ECPSSR theory has been found to give good agreement with the experimental data while the first Born theory over-predicts the cross sections at all the measured energies , Andrews et al 1987.…”
Section: Introductionmentioning
confidence: 64%
“…Andrews et al (1987) have reported the M-shell x-ray production cross sections in Pb by 25 MeV 12 C q+ (q = 4, 5, 6) and by 32 MeV 16 O q+ (q = 5, 7, 8) ions. In two different measurements, Mehta et al (1982Mehta et al ( , 1983 measured the M x-ray production cross sections in Pb and Bi bombarded by protons and 4 He + ions of 0.3-2.6 MeV and by fluorine ions of charge states 4, 5, 6, 8 and 9 and energies of 25, 27 and 35 MeV. de Castro Faria et al (1983) have measured the M-subshell ionization cross sections of Pb and Bi by protons impact over the energy range 0.3-4.0 MeV while Price et al (1988) have reported the M-shell x-ray production cross sections for 9 Be + ions of energies 0.5-2.5 MeV incident upon Pb and Bi targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While PIXE originated and continues using light ions such as protons or alphas [6][7][8][9][10][11][12][13][14][15][16],there is an increasing interest to use heavy ions for PIXE analysis due to higher cross sections and thereby better sensitivity [17]. While discrepancies between theories and experiment were attributed to multiple ionization even with protons [18], multiple-ionization effect has been known for decades in L-shell ionization by heavier ions [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. However this effect is still rarely addressed for the x-ray emission elemental analysis in the aftermath of ionization by such ions.…”
Section: Introductionmentioning
confidence: 99%